Population pharmacokinetics of cefazolin in critically ill children infected with methicillin-sensitive Staphylococcus aureus. (March 2021) - Salvador, E.; Oualha, M.; Bille, E.; Beranger, A.; Moulin, F.; Benaboud, S.; Boujaafar, S.; Gana, I.; Urien, S.; Zheng, Y.; Toubiana, J.; Briand, C.; et al.
Abstract: Objectives: Cefazolin is one of curative treatments for infections due to methicillin-sensitive Staphylococcus aureus (MSSA). Both growth and critical illness may impact the pharmacokinetic (PK) parameters. We aimed to build a population PK model for cefazolin in critically ill children in order to optimize individual dosing regimens. Methods: We included all children (age < 18 years, body weight (BW) > 2.5 kg) receiving cefazolin for MSSA infection. Cefazolin total plasma concentrations were quantified by high-performance liquid chromatography. A data modelling process was performed with the software MONOLIX. Monte Carlo simulations were used in order to attain the PK target of 100% fT > 4 × MIC . Results: Thirty-nine patients with a median (range) age of 7 (0.1–17) years and a BW of 21 (2.8–79) kg were included. The PK was ascribed to a one-compartment model, where typical clearance and volume of distribution estimations were 1.4 L/h and 3.3 L respectively. BW, according to the allometric rules, and estimated glomerular filtration rate (eGFR) on clearance were the two influential covariates. Continuous infusion with a dosing of 100 mg/kg/day to increase to 150 mg/kg/day for children with a BW < 10 kg or eGFR >200 mL/min/1.73m 2 were the best schemes to reach the PK target of 100% fT > 4 × MIC . Conclusions: In critically ill children infected with MSSA, continuous infusion seems to be the most appropriate scheme to reach the PK target of 100 % fT > 4 × MIC in children with normal and augmented renal function.